Optimal Integrated Inner Controller Design in AC Microgrids - Batmani, Yazdan; Khayat, Yousef; Najafi, Shahabeddin; Guerrero, Josep M. (IEEE transactions on power electronics, 2022)
The optimal design of a microgrid's primary control's inner loops is a severe challenge in high-bandwidth (BW) applications. Mostly, nonoptimal controllers are given as a sublevel design for the current and voltage inner loops. Unlike conventional methods, such as proportional resonant, proportional-integral, and finite-set model predictive control, in this article, an optimal integrated inner controller is proposed based on a linear quadratic tracking (LQT) methodology. In the proposed method, a model-based optimal LQT controls the microgrid's voltage and current simultaneously. By employing this method, a performance index, which is a system energy indicator is minimized, and the BW of the controller is systematically adjusted through the employed weighting matrices in the performance index. Besides, a current limiting mechanism is provided for the proposed method, which discriminates its applicability for practical purposes. Unlike the conventional current limiting algorithms, which limit the sine-waveform of the current, the proposed method limits the amplitude of the current and causes less current and voltage distortions during over-current situations. The simulation and experimental results reveal the superiority of the proposed method.